Global compact attractors and complete bounded trajectories for compressible magnetohydrodynamic system of equations - Muhammad Jan (Theoretical and Applied Mechanics)
In this article, we investigate the global behavior of magnetohydrodynamic (MHD) fluid’s weak solutions in three-dimensional bounded domain with a compact Lipschitz boundary driven by arbitrary forces. We show that global compact attractors exist under specific limitations on the adiabatic constant γ.